RELEVANCE OF THE DUAL MODEL OF VALUES IN RELATION TO THE PREJUDICE AND THE CONTACT INTENTION TOWARD OUTGROUPS - Martínez Martínez, Mª del Carmen; Paterna Bleda, Consuelo; Gouveia, Valdiney V. (Anales de Psicología / Annals of Psychology, 2006)
The investigation on the role of values in intergroup relations has been focused on two hypothesis, congruence and difference. While the first one identifies those values which promote and inhibit the prejudice, the second one assumes that is the difference in the values among groups the origin of prejudice. This article shows, from congruence hypothesis and new approach about racism, the relationship among values, prejudice and contact intention. Participated in the research 209 subjects, with a mean age of 30 years old (136 women; 73 men). The results indicated that the values are adequate predictors for both prejudice and contact intention toward gypsies. According to the new approaches, study purpose a dual model of values related to prejudice.